If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3(x + -3) = -2(-2 + -1x) Reorder the terms: -3(-3 + x) = -2(-2 + -1x) (-3 * -3 + x * -3) = -2(-2 + -1x) (9 + -3x) = -2(-2 + -1x) 9 + -3x = (-2 * -2 + -1x * -2) 9 + -3x = (4 + 2x) Solving 9 + -3x = 4 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 9 + -3x + -2x = 4 + 2x + -2x Combine like terms: -3x + -2x = -5x 9 + -5x = 4 + 2x + -2x Combine like terms: 2x + -2x = 0 9 + -5x = 4 + 0 9 + -5x = 4 Add '-9' to each side of the equation. 9 + -9 + -5x = 4 + -9 Combine like terms: 9 + -9 = 0 0 + -5x = 4 + -9 -5x = 4 + -9 Combine like terms: 4 + -9 = -5 -5x = -5 Divide each side by '-5'. x = 1 Simplifying x = 1
| 560x(x)=70 | | 7-8x=135 | | 3p^2=3p+6 | | 50x^2+25x-3=0 | | 10k^2-4K-32=-11 | | (m-5)(m-5)=13 | | 4-5/2b=a8-5b | | 4w+5=2w+13 | | 8x-96=-6x+128 | | 3(x+3)=-3(2-x) | | 4/(7-i) | | 5n^2-25=20n | | 2.68x^2+4.75=-2.25 | | 7n^2+39-18=0 | | 9y^3-21y^2-18y=0 | | x^2+7=67 | | (8x^2-2x+7)+(4x^3-4x)=0 | | 31/5x=-7 | | 5x+8+4x+1=180 | | 8-4r=-2-1 | | X÷8/9=21 | | 0.5x+10=54 | | 5m^2-36m+36=0 | | X÷8/8=21 | | 2x+1=6x-7 | | 5b+3=4b | | 4n+5=47-3n | | .36666*(11/2) | | 24x^3-56x^2+15x-35=0 | | 2(k-4)=(2k-8) | | 3u-11=46 | | 3(2x-18)=31+x |